Phylogenetic analysis of Quercus L. species with three DNA barcode genetic markers: The phylogeny of Quercus L. species - Pacheco-Reyes, Flor Cristina; Wei, Lihua; Perez-Rodriguez, Miguel Angel (Ecosistemas y Recursos Agropecuarios, 2021)
The genus, Quercus L, Fagaceae has great relevance in terms of diversity, ecological and economic importance. However, the recorded taxonomicinformation does not always distinguish the classification. In this study, three DNA regions (rbcL, matK and ITS2) were used as barcodes to identify species of the genus Quercus. The analyzed data (56 rbcl, 51 ITS and 61 matK sequences) corresponded to 92 species (11 are from Mexican, and 81 are from Eurasia and North America). The universal primers (rbcL and ITS2) amplified 100% of Mexican oak samples. The BLAST analysis of the rbcL and ITS2 fragments of Mexican oaks, showed a high identification ability with 98.1 and 98.3% respectively. Genetic distance-based method resulted in extremely low discrimination rates, possibly due to overlapping genetic distances, as well as frequent inter-species hybridization anda low rate of variation. The neighbor-joining method provided a high discriminatory ability with matK (81.96%) and ITS2 (80.39%) markers, generating groupings based on geographic regions and sections of the Quercus subgenus in phylogenetic trees. According to the overall performance, ITS2 and matK are recommended to use as the most suitable DNA barcodes to identify Quercus species.